The Influence of the Project Based Learning Model on Science Learning Outcomes in Class V Students at MIS Al Huda Langkat - Pandiangan, Enda Lovita; Harahap, Muhammad Arfan (LPPPI Publishing, 2024)
This research aims to determine the science learning outcomes of students by applying the project based learning model in class V MIS AL Huda, Langkat. This type of research is quasi-experimental with a pretest and posttest control group design. The population of this study was all students in class V of MIS AL Huda, Langkat, totaling 30 students. The sampling technique used was probability sampling with a stage random sampling technique, namely 30 students were sampled as part of the population. The instrument used is a test sheet to measure student learning outcomes. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis with the independent sample test. Based on the results of the descriptive analysis, the average obtained for the two groups, in the control class before and after implementing the project based learning model, was a pretest score of 54.33 and a posttest score of 76.33. In the experimental class by applying the project based learning model, the pretest average was 43.33 and the posttest average was 71.33. Based on the results of the independent sample-test, it shows that the t test value with a sig value < a = 0.05 (0.000 < 0.05) indicates that H1 is accepted. The results of the research show that there is a significant difference between the experimental class (VA) applying the project based learning model and the control class (VB) on science learning outcomes for MIS AL Huda, Langkat students.